1987
DOI: 10.1002/rrr.3450010103
|View full text |Cite
|
Sign up to set email alerts
|

The distribution and management of channelized streams in Denmark

Abstract: The Danish Watercourse Law of 1982 states that major river works and maintenance procedures must be planned and undertaken with regard to water quality and the physical form of the river channel. Fluvial geomorphology is an essential component of alternative procedures of river management which work with nature rather than against it. A survey of Danish stream channels has been produced by collating data obtained from maps, field surveys and engineering documents. This indicates that 97.8 per cent of Danish wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0
13

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(75 citation statements)
references
References 12 publications
1
61
0
13
Order By: Relevance
“…Brookes (1987b) to aggradation and/or degradation with only partial recovery, whereas the rivers studied below this range of stream power had insufficient energy for natural morphological adjustment to occur. The majority of channelisation schemes are found in lowland zones with some degree of urbanisation and agricultural expansion within the catchment.…”
Section: V) Impeded Natural Recoverymentioning
confidence: 97%
See 1 more Smart Citation
“…Brookes (1987b) to aggradation and/or degradation with only partial recovery, whereas the rivers studied below this range of stream power had insufficient energy for natural morphological adjustment to occur. The majority of channelisation schemes are found in lowland zones with some degree of urbanisation and agricultural expansion within the catchment.…”
Section: V) Impeded Natural Recoverymentioning
confidence: 97%
“…This type of intense management was not just confined to the U.K., with similar flood control management practises in many European countries (Brookes, 1987b(Brookes, , 1988(Brookes, , 1990Iversen et al, 1993), in the U.S.A. (Little, 1973;Winkley, 1982) and elsewhere. For example, intensive farming and urban development in Denmark have left only 2.2 percent of rivers with sinuous courses, most of which are large rivers that are difficult to regulate and reaches unsuited for agricultural development (Brookes, 1987b(Brookes, , 1988. By providing legislation for new land drainage works, the Land Drainage Acts of 1861 and 1930 have played important roles in shaping the river landscape in the U.K. as it is viewed today.…”
Section: Iv) Flood Banksmentioning
confidence: 99%
“…Based on streams in England, Wales and Denmark, Brookes [114,115] revealed that post-project adjustment of channelised rivers can be related to stream power, whereby values less than approximately 15-25 W·m −2 correspond to projects that experienced deposition and values greater than approximately 25-35 W·m −2 correspond to projects that responded predominantly through erosion. This approach was developed into the 'stream power screening tool' [4,35], a bankfull-level assessment with the purpose of rapidly identifying potential sediment issues along a river network and prioritising reaches for further geomorphological investigation.…”
Section: Stream Energy Approaches In Fluvial Studies: Underpinning Comentioning
confidence: 99%
“…Instream physical habitat is vulnerable to management activities such as water abstraction impacts on low flow conditions in summer (Henriksen et al, 2008;Olsen et al, 2009), directly impacting on water depth and water velocity. Physical modification of the streams (Brookes, 1987) directly impacts depth and water velocity but also substrate and cover attributes (e.g. boulders, wood) which are closely affiliated with stream management actions, including restoration in small lowland streams.…”
Section: P11mentioning
confidence: 99%
“…These small streams are important rearing areas for anadromous salmonid populations including brown trout (Salmo trutta) (Mortensen, 1977;Heggenes et al, 2002;Roussel and Bardonnet, 2002). Small streams are also particularly vulnerable to human impact such as water abstraction, agriculture, forestry, and channelisation (Brookes 1987;Olsen et al, 2009;Falke et al, 2011;Procopio, 2012) or the potential effects of climate change (Almodóvar et al, 2012;Bain and Jia 2012). Because brown trout are important socially, economically and ecologically within much of Europe, they are often used as the 'fish' indicator species for many of the national and EU environmental plans in both large rivers and small streams (Friberg et al, 2005;Conallin, 2009).…”
Section: Introductionmentioning
confidence: 99%